THE ROLE OF THE SHARIA SUPERVISORY BOARD (DPS) IN IMPLEMENTING SHARIA PRINCIPLES IN BAITUL MAAL WA TAMWIL (BMT) PRODUCTS - Ma'unatun Nadhifah, Nadhifah (Fakultas Ekonomi dan Bisnis Islam, 2022)
Abstract As a sharia economic entity, the entire business and activity of BMT must comply with the provisions of the MUI DSN fatwa. To ensure the implementation of the application of sharia principles to products within the BMT institution. Thus the role of DPS is very important because it ensures that BMT in its operations is in accordance with sharia provisions or not. This study aims to analyze what kind of supervision is carried out by DPS in BMT. This study uses a descriptive qualitative method with an interview method approach with data collection obtained through interview information by the informant manager, AO, Teller from BMT. The results of this study show that there are still obstacles faced by the DPS in carrying out supervision due to several factors, namely limited human resources and the age factor of DPS members. These results provide recommendations to DPS to develop its performance in conducting supervision. Keywords: Sharia Supervisory Board, BMT, Sharia Principles